The correlation between the pelvic movement symmetry during motion, as well as body mass and the alignment of the knees of school children - Wojtanowski, Wiesław; Kozioł, Paulina; Jankowicz-Szymańska, Agnieszka (Health Promotion & Physical Activity, 2020)
Introduction: Body posture, including the alignment of the knees, as well as being overweight or obese, has a measurable influence on the way one moves. Most of the somatic and motor dysfunctions, which are often a problem for adults, originated in their childhood. Ailments regarding motor functions among adults are often a consequence of a previously overlooked or untreated dysfunction. Children and teenagers are a large group of patients suffering from dysfunctions of such type. The goal of this research was to assess the degree of influence being overweight or obese and having valgus knees has over children’s pelvic movement symmetry during motion. Materials and methods: 192 primary school students, aged 11-13, from Tarnow and its surrounding areas took part in the study. The alignment of their lower limbs was realised through measuring the distances between their medial malleoli, while standing up, with legs joined at knees. The pelvic movement symmetry while walking was tested with the BTS G-Walk device. Results: Boys have been diagnosed with having excessive body weight and valgus knees alignment more often than girls. A crucial correlation between being overweight or obese and having valgus knees was noted. A notable difference in the pelvic movement symmetry during motion between overweight or obese children and those with correct body weight, as well as between children with valgus and correct knees alignment has been determined. Studying the correlation coefficient has shown that BMI is more relevant than knee alignment to the problem in question. Conclusion: Gait re-education should be a part of kinesitherapy both for the children with valgus knees and those with excessive body weight.